HYPOTACTIC STRUCTURE IN ENGLISH - Kurniasy, Dessy (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2016)
This present study focuses on the study of a hypotactic structure in English. It is concerned with clause complex which is comprised of two or more clauses logically connected. The relation between clauses can be interpreted in terms of ‘logical’ semantic relations and system of interdependency relation – parataxis and hypotaxis. The method used in this study was qualitative approach in which the data were taken from some linguistic books. The finding shows that the concept of hypotactic structure in English is divided into two types: expansion and projection. There are three kinds of expanding a clause i.e. elaboration (=), extension (+) and enhancement (x), and two kinds of projection i.e. locution (”) and idea (’). Elaboration shows that the meaning of the secondary clause is equal to the primary one, but the secondary clause does not introduce a new element into the picture but rather provides a further characterization of one that is already there. Extension is a clause that extends the meaning of another by adding something new to it. Meanwhile, enhancement shows the meaning of another clause by qualifying it with adverbial clause in traditional grammar. Furthermore, the three clauses can be finite or non-finite. Locution, on the other hand, is a projection with verbal process, in which the clause containing the sayer and the reporting verb is thedominant clause and the reported element is the dependent clause. Thus, idea is a projection with mental process that is used to report ideas, beliefs, fears and speculations. The combination of mental process with a dependent ‘reporting’ clause is the nominal ways of representing what people say, think and believe.